Panic Disorder and Agoraphobia: A Case Study (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
The objective of the present study was to intervene in the problematic behaviors of a 53-year-old client who reported to the therapist to experience bodily states compatible with manifestations of panic disorder. Based on the verbal reports and records of the client's behaviors, the therapist described the contingencies that produced the client's complaint and taught the client that anxiety is a bodily state produced by aversive contingences to which she responded. During the intervention process, the client acquired the repertoire needed to respond appropriately to the aversive contingencies. The client's maladaptive behaviors became under the control of the therapeutic procedures.